Pengembangan E-Booklet Aktivitas Antioksidan Krim Sari Buah Naga Merah (Hylocereus polyrhizus) sebagai Materi Pengayaan Bioproses Sel : Developing The Biology E-booklet based on Antioxidant Activity Of Red Dragon Fruit (Hylocereus polyrhizus) for Bioprocess Cell enrichment material - Raja, Angraini Ahza Sazwita; Novi Febrianti; Ardiansyah , Ryan (JURNAL BIOSHELL, 2022)
E-Booklet learning resource from study results for enrichment materials are still limited . This study aims to determine the quality and feasibility of the antioxidant activity of red dragon fruit juice (Hylocereus polyrhizus) E-Booklet as an enrichment material for class XI of cell bioprocessing. The subjects of this study were students of class XI IPA SMA Negeri 5 Yogyakarta. E-Booklet development is adapted from 4D models (define, design, develop, and disseminate). Likert scale questionnaire  was used to assess the product and the guttman scale questionnaire was used to determine student responses. Product assessment was carried out by media experts, material experts, and Biology teacher at SMA Negeri 5 Yogyakarta. The product trial data was taken from 34 students of SMA Negeri 5 Yogyakarta. Data from the assessment questionnaire were analyzed descriptively to determine the quality of the E-Booklet. The results of the assessments from material experts, media experts and biology teachers indicate that the quality of the E-Booklets that have been arranged is in the very good category, so it is appropriate to proceed to the product trial stage. The student responses indicate E-Booklet was in the very good category.